A large-scale physical model test on frozen status in freeze-sealing pipe roof method for tunnel construction. (February 2018) - Hu, Xiangdong; Fang, Tao; Chen, Jin; Ren, Hui; Guo, Wang
Highlights: Freeze-sealing pipe roof method is employed for Gongbei Tunnel for the first time. An innovative freezing scheme is implied by three different types of freezing tubes. A physical model test was conducted to validate the freezing effect of FSPR. The results of different construction periods have been analysis. The effectiveness of freezing scheme is proved by the model test. Abstract: The Gongbei Tunnel, the most important and difficult part in Zhuhai Link of Hong Kong-Zhuhai-Macao Bridge, faces numerous troubles because of natural and human-related factors. A new pre-supporting technique, Freeze-Sealing Pipe Roof method, which combines Pipe-Roofing Method with Artificial Ground Freezing method, has been put forward and employed for the first time in China during the construction of the Gongbei Tunnel. An innovative freezing scheme is proposed by three kinds of freezing tubes (master, enhancing and limiting tubes) to cope with various conditions. A large-scale physical model test has been conducted so as to validate the freezing effect of Freeze-Sealing Pipe Roof method. The present paper focuses on the experimental set-up and results in detail, which confirms safety and rationality of the freezing scheme.